2021
DOI: 10.52562/jdle.v1i01.27
|View full text |Cite
|
Sign up to set email alerts
|

Indonesian Learning Through WhatsApp Group To Create Interactive Learning Conditions

Abstract: This research aims to use WhatsApp group to Indonesian learning in VIII class students at UPT SMP Negeri 3 Ponggok. This research used qualitative approach because it uses data in the form of words. At the same time, this research used experimental type because it is testing something. The research subjects were from VIII-D class students, and the object was Indonesian learning through WhatsApp group. The data collection techniques were observation, documentation, and questionnaires. Comparative analysis will … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
1
1
0
1
Order By: Relevance
“…This is also supported by implementing classrooms in the form of Whatsapp groups. The research that obtained similar results was the research of Santoso & Dewi (2021). Based on this research, the use of Whatsapp groups has the advantage of making learning more interactive than Google Classroom.…”
Section: The Obstacles Of Learningsupporting
confidence: 53%
“…This is also supported by implementing classrooms in the form of Whatsapp groups. The research that obtained similar results was the research of Santoso & Dewi (2021). Based on this research, the use of Whatsapp groups has the advantage of making learning more interactive than Google Classroom.…”
Section: The Obstacles Of Learningsupporting
confidence: 53%
“…The reason the teacher raised the topic of ideals to be included in the pesawat kertas game was because ideals could encourage students' enthusiasm for learning. Gulo also once revealed that the ideals in students have a positive influence on learning motivation [27]. While writing was in progress, the other students were instructed to join in hoping that their friend's dreams would succeed and say "aamiin".…”
Section: The Pesawat Kertas Gamementioning
confidence: 99%
“…Pandemi covid-19 membuat pembelajaran di Indonesia menjadi berbasis daring (Santoso & Dewi, 2021). Hal tersebut membuat kurikulum yang sudah ditentukan megalami sebuah fleksibilitas sesuai dengan kondisi siswa dan sekolah.…”
Section: Pendahuluanunclassified